2014
DOI: 10.12944/cwe.9.1.02
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Trace Elements Levels in Sediment and Water in Some Artisanal and Small-Scale Mining (ASM) Localities in Ghana

Abstract: The concentrations of eight trace elements, Cadmium (Cd), lead (Pb), iron (Fe), zinc (Zn), manganese (Mn), copper (Cu), mercury (Hg) and arsenic(As) in sediment and water were assessed in four artisanal and small-scale mining(ASM) localities in the Amansie West District (6°282 N 1°532 W) of Ghana along two river courses from May 2011 to July 2011. Triplicate water and sediment samples were randomly taken at five different points at each of the localities and the elements determined using Atomic Absorption Spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Agyarko et al (2014) found Cd, Pb, Cu and Hg in sediment samples from two river courses under the influence of small-scale mining in the Amansie West District of Ghana. The maximum concentrations they reported were 760 g/kg (Cd), 10,600.0 g/kg (Pb), 101,150.0 g/kg (Cu) and 46,600 g/kg (Hg).…”
Section: Toxic Metals In Waste Stabilization Pondsmentioning
confidence: 93%
“…Agyarko et al (2014) found Cd, Pb, Cu and Hg in sediment samples from two river courses under the influence of small-scale mining in the Amansie West District of Ghana. The maximum concentrations they reported were 760 g/kg (Cd), 10,600.0 g/kg (Pb), 101,150.0 g/kg (Cu) and 46,600 g/kg (Hg).…”
Section: Toxic Metals In Waste Stabilization Pondsmentioning
confidence: 93%
“…More specifically, the harvesting of B. aethiopum fruits for hypocotyl production and trade has become, over the last two decades, one of the most important household commercial activities associated with this species in Benin, West Africa [33]. Further fragmentation of the species’ habitat has been observed as result of land clearing for agriculture or urban development [32,34,35]. As illustrated through similar examples in the literature [39,40], such phenomena may lead to restricted gene flow and ultimately, to loss of genetic diversity among B. aethiopum populations.…”
Section: Introductionmentioning
confidence: 99%
“…These multiple uses of products derived from B. aethiopum have put a strong anthropogenic pressure on the species, thus contributing to both fragmentations of its populations and their poor natural regeneration [27,[29][30][31][32]. Further fragmentation of the species' habitat has been observed as a result of land clearing for agriculture or urban development [32][33][34]. As illustrated through similar examples in the literature [35,36], such phenomena may lead to restricted gene ow and ultimately, to loss of genetic diversity among B. aethiopum populations.…”
Section: Introductionmentioning
confidence: 99%